ANALYSIS OF CASH WAQF FUND COLLECTION STRATEGY AND MAANGEMENT PROBLEM - Amaruddin, Amin Awal; Effendi , Arta Zulian; Ashlihah, Ashlihah (Izdihar: Jurnal Ekonomi Syariah, 2026)
Cash waqf has significant potential to support education and social welfare but its implementation in Indonesia still faces challenges in fundraising and management. This study examines the strategies, empowerment models, and managerial issues of cash waqf at the Center for Social Fund Management, Universitas Airlangga (PUSPAS UNAIR). Using a qualitative case study, data were collected through interviews and documentation, validated by triangulation, and analyzed with Miles and Huberman’s interactive model. Findings show three fundraising strategies: direct (open booths, parent meetings, crowdfunding), indirect (social media, flyers, webinars), and incentive-based (rewards for waqifs). The funds are utilized for living cost assistance, dormitories, productive enterprises, and scholarships. Key challenges include limited human resources, weak innovation, low literacy, lack of university support, and infrastructure constraints. The study recommends strengthening nazhir professionalism, investment mechanisms, and waqf literacy to sustain cash waqf in higher education.   Keywords: cash waqf, fundraising, empowerment, management, higher education